2007
DOI: 10.1074/jbc.m610669200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase D Induces Transcription through Direct Phosphorylation of the cAMP-response Element-binding Protein

Abstract: Protein kinase D (PKD), a family of serine/threonine kinases, can be activated by a multitude of stimuli in a protein kinase C-dependent or -independent manner. PKD is involved in signal transduction pathways controlling cell proliferation, apoptosis, motility, and protein trafficking. Despite its versatile functions, few genuine in vivo substrates for PKD have been identified. In this study we demonstrate that the transcription factor cAMPresponse element-binding protein (CREB) is a direct substrate for PKD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 79 publications
2
52
0
1
Order By: Relevance
“…5), which may reflect an inhibitory effect of certain PKC. These data suggest that transcription and/or stabilization of CCL2 mRNA is downstream of PKD1 activation, consistent with reports in other cell types that activation of PKD1 fosters gene transcription through regulation of class II histone deacetylases and/or transcription factors (33)(34)(35)(36)(37)(38). The effects of PKD1 activation also extended to the release of CCL2 protein induced by Pam3CSK4, SCF, and cross-linked IgE, as they showed the identical pharmacologic profile measured 2 h after cell activation (Fig.…”
Section: Figuresupporting
confidence: 89%
See 1 more Smart Citation
“…5), which may reflect an inhibitory effect of certain PKC. These data suggest that transcription and/or stabilization of CCL2 mRNA is downstream of PKD1 activation, consistent with reports in other cell types that activation of PKD1 fosters gene transcription through regulation of class II histone deacetylases and/or transcription factors (33)(34)(35)(36)(37)(38). The effects of PKD1 activation also extended to the release of CCL2 protein induced by Pam3CSK4, SCF, and cross-linked IgE, as they showed the identical pharmacologic profile measured 2 h after cell activation (Fig.…”
Section: Figuresupporting
confidence: 89%
“…Particularly notable are the findings that phosphorylation of histone deacetylases 5 and 7 by PKD1 regulates their export from the nucleus, leading to derepression of the transcription of certain genes (33)(34)(35)(36)(37). In addition, PKD1 phosphorylates members of the cAMP-response elementbinding protein family of transcription factors, leading to increased transcriptional activity (38). PKD1 belongs to a family of three homologous enzymes (6,39,40) that can differ in subcellular localization (41)(42)(43) and function (29,37,44).…”
mentioning
confidence: 99%
“…However, the list of known PKD substrates remains relatively short. We and others recently implicated PKD as a CREB-Ser 133 kinase that regulates Cre-dependent transcriptional responses (6,7). PKD also functions as a physiologically relevant HDAC5 kinase (8).…”
Section: Protein Kinase D1 (Pkd1)mentioning
confidence: 98%
“…PKD-mediated transcriptional control can occur through at least two mechanisms. PKD directly phosphorylates the transcription factor CREB to allow recruitment of coactivators, including CREB binding protein (CBP)/p300, and augment CREB-mediated gene expression (26). In a recent study, CREB dependent transcription of the immediate-early gene, Nurr1, was found to be important for in vivo angiogenesis in a mouse model using matrigel plugs (27).…”
Section: Pkd Function In Endothelial Cellsmentioning
confidence: 99%